The labor culture of Madurese siwalan farmers: morality and attitude - Muhamad Abdul Jumali; Anita Kristina; Khairunisah binti Kamsin (Agriekonomika, 2026)
This qualitative study explores the labor culture of siwalan farmers in Madura, Indonesia, highlighting how religious values and prayer practices are integrated into daily agricultural routines. Departing from conventional productivity metrics, it examines how adherence to Islamic principles particularly respecting prayer times defines work ethic and productivity within this community. Based on in-depth interviews and observations, the study reveals how spirituality shapes decision-making, work schedules, and attitudes toward labor. The findings emphasize the role of religious commitment in guiding agricultural activities, suggesting that spiritual fulfillment is central to productivity and well-being. This research contributes to a nuanced understanding of indigenous work cultures in Indonesia, especially how religious frameworks shape perceptions of labor beyond economic measures. Insights from this study are also valuable for policymakers and development practitioners engaging with agricultural communities, and they enrich broader academic discussions on the intersection of religion, work, and economy in non-Western contexts.